Do polystyrene nanoplastics affect the toxicity of cadmium to wheat (Triticum aestivum L.)? - Lian, Jiapan; Wu, Jiani; Zeb, Aurang; Zheng, Shunan; Ma, Ting; Peng, Feihu; Tang, Jingchun; Liu, Weitao (Environmental pollution (1987), 2020)
There has been an increase on the research of microplastics (<5 mm in diameter) as carriers for toxic chemicals to evaluate their risks for human health and environment, but only few works focused on nanoplastics (1 nm–1000 nm in diameter) interacting with pre-existing contaminants such as heavy metals. It is still unclear whether polystyrene nanoplastics (PSNPs) could affect the toxicity of cadmium to wheat (Triticum aestivum L.). Here, we assessed the impact of polystyrene nanoplastics (0, 10 mg/L) on the Cd (0, 20 μM) toxicity to wheat grown in 25% Hoagland solution for three weeks. We found that the presence of PSNPs could partially reduce Cd contents in leaves and alleviate Cd toxicity to wheat, which might be due to weakened adsorption capacity of PSNPs affected by ionic strength. In addition, PSNPs have little effect on catalase (CAT), peroxidase (POD) activities, except for decreasing superoxide dismutase (SOD) activity, which suggested that antioxidant defense systems might not be the main mechanism to reduce the oxidative damage induced by Cd in wheat. Electron paramagnetic resonance (EPR) analysis showed that PSNPs could accelerate the formation of long-lived radicals in leaves after exposure to Cd. Notably, our metabolomics profiling further indicated that the simultaneously elevated carbohydrate and amino acid metabolisms induced by PSNPs could partly alleviate Cd toxicity to wheat. Nevertheless, the present study provides important implications for the toxicological interaction and future risk assessment of co-contamination of nanoplastics and heavy metals in the environment. [Display omitted] •PSNPs reversibly adsorbed Cd but adsorption is significantly weakened by ionic strength.•Cd-induced toxicity in wheat could be partly alleviated by PSNPs.•PSNPs did not markedly improve antioxidant enzyme activities under Cd treatment.•Carbohydrates and amino acid metabolisms were elevated by PSNPs to resist Cd toxicity.